2017
DOI: 10.1016/j.actatropica.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alters the cytoskeleton and microtubule organization on trophozoites of Giardia lamblia

Abstract: Giardia lamblia is a worldwide protozoan responsible for a significant number of intestinal infections. There are several drugs for the treatment of giardiasis, but they often cause side effects. Curcumin, a component of turmeric, has antigiardial activity; however, the molecular target and mechanism of antiproliferative activity are not clear. The effects of curcumin on cellular microtubules have been widely investigated. Since tubulin is the most abundant protein in the cytoskeleton of Giardia, to elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 55 publications
1
15
0
2
Order By: Relevance
“…A monoclonal anti-α-tubulin antibody revealed that these lignans provoked changes in the distribution and staining pattern of microtubular structures, in a dose-dependent manner (Figure 1). It was associated with a decrease in the polymerized tubulin fraction (Figures 2 and 3); similar results were observed with albendazole, a drug that inhibits microtubule polymerization (Aguayo-Ortiz et al, 2013;Gutiérrez-Gutiérrez, Palomo-Ligas, et al, 2017;Pérez-Rangel et al, 2013). Besides, our results agree with previous findings in mammalian cells, showing that podophyllotoxin-type lignans affect the expression and stability of polymerized tubulin (Kamal et al, 2014;Prinz et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…A monoclonal anti-α-tubulin antibody revealed that these lignans provoked changes in the distribution and staining pattern of microtubular structures, in a dose-dependent manner (Figure 1). It was associated with a decrease in the polymerized tubulin fraction (Figures 2 and 3); similar results were observed with albendazole, a drug that inhibits microtubule polymerization (Aguayo-Ortiz et al, 2013;Gutiérrez-Gutiérrez, Palomo-Ligas, et al, 2017;Pérez-Rangel et al, 2013). Besides, our results agree with previous findings in mammalian cells, showing that podophyllotoxin-type lignans affect the expression and stability of polymerized tubulin (Kamal et al, 2014;Prinz et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…A recent work shows that CUR reduces growth in E. histolytica [ 10 ] and in G. lamblia. [ 11,32 ] However, although CUR shows excellent pharmacological qualities, its clinical use is limited, due to the low solubility in water [ 12,13 ] ; thus, limiting their bioavailability and poor systemic absorption in the digestive tract, this promotes poor pharmacokinetics in vivo , which affects their pharmacological effect. [ 14,15 ] Another drawback is that CUR is an unstable molecule, which may suffer degradation by light, [ 6,13,16,18 ] making the pharmacological management difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8,9 ] Recently, Rangel‐Castañeda and coworkers demonstrated that 100–300 µ m of CUR has amoebicidal activity, affecting Entamoeba histolytica trophozoites, growth, and morphology, in a dose‐dependent behaviour, [ 10 ] in Giardia lamblia CUR inhibits the growth by affecting the microtubules; dramatic changes on cell morphology and loss of attachment were observed. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vivo effects of curcumin treatments were also documented in rabbit and sheep coccidiosis (27, 28). Overall, the molecular mechanism of curcumin action is not known so far, but interference with intracellular organelles and cytoskeleton or with cellular metabolism is postulated (29), which might impact on protozoan parasites. Furthermore, curcumin inhibits the glyoxalase system of T. gondii (24) and efficiently blocks histone deacetylation in curcumin-exposed P. falciparum (25).…”
Section: Introductionmentioning
confidence: 99%